On-surface synthesis of π-conjugated ladder-type polymers comprising nonbenzenoid moieties - Urgel, José; Bock, Julian; Di Giovannantonio, Marco; Ruffieux, Pascal; Pignedoli, Carlo A.; Kivala, Milan; Fasel, Roman (RSC Advances, 2021)
On-surface synthesis provides a powerful approach toward the atomically precise fabrication of pi-conjugated ladder polymers (CLPs). We report herein the surface-assisted synthesis of nonbenzenoid CLPs from cyclopenta-annulated anthracene monomers on Au(111) under ultrahigh vacuum conditions. Successive thermal annealing steps reveal the dehalogenative homocoupling to yield an intermediate 1D polymer and the subsequent cyclodehydrogenation to form the fully conjugated ladder polymer. Notably, neighbouring monomers may fuse in two different ways, resulting in six- and five-membered rings, respectively. The structure and electronic properties of the reaction products have been investigated via low-temperature scanning tunneling microscopy and spectroscopy, complemented by density-functional theory calculations. Our results provide perspectives for the on-surface synthesis of nonbenzenoid CLPs with the potential to be used for organic electronic devices.